Junior Code Academy: A pilot project - Moreira, Filipe; Barbosa, Isabel; Loureiro, Maria Joao; Pombo, Lucia; Loureiro, Maria Jose (2015 International Symposium on Computers in Education (SIIE), 2015)
The Junior Code Academy is a pilot project that aims to generalize the teaching of programming and code in schools in Portugal, promoting digital literacy and developing skills of problem solving. The presented qualitative pilot study involves students from the 1st cycle of basic education in three schools of Lisbon Municipality, comprising partnership with Calouste Gulbenkian Foundation and University of Aveiro. The main preliminary results emphasized that there is a high motivation and commitment of students towards programming, which potentially prevents early school dropout.